2020
DOI: 10.1097/pep.0000000000000663
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Change in Common Impairments in Children With Cerebral Palsy From Age 1.5 to 11 Years

Abstract: This project aimed to determine if change occurs over time for impairments of balance, range of motion (ROM), endurance, and strength of children with cerebral palsy (CP), by Gross Motor Function Classification System (GMFCS) levels. MethodsMeasurements were completed in 77 children at two sessions (T1, T2) on average 5.8 years apart. Mean ages were 2.9 years (SD .9) and 8.7 years (SD 1.1) at T1 and T2, respectively. ResultsSignificant differences were noted from T1 to T2 for some children (GMFCS levels I, II,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 36 publications
0
10
0
7
Order By: Relevance
“…All components of the ICF were investigated, with most of the studies reporting longitudinal outcomes in more than one component (Figure 1). The activity component was the most investigated (67.9%, n = 38 studies), 16,17,31,32,34–36,38,39,41,46,47,49–51,53,54,56,58,60–66,68,70–72,76–83 followed by body functions and structures (42.9%, n = 24 studies) 32,34,37–39,41,43–45,47,48,51,52,55–59,66,69,73,74,82,84 . Participation (14.2%, n = 8 studies) 33,40,42,48,52,67,75,78 and environmental factors (3.6%, n = 2 studies) 33,42 were the least studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All components of the ICF were investigated, with most of the studies reporting longitudinal outcomes in more than one component (Figure 1). The activity component was the most investigated (67.9%, n = 38 studies), 16,17,31,32,34–36,38,39,41,46,47,49–51,53,54,56,58,60–66,68,70–72,76–83 followed by body functions and structures (42.9%, n = 24 studies) 32,34,37–39,41,43–45,47,48,51,52,55–59,66,69,73,74,82,84 . Participation (14.2%, n = 8 studies) 33,40,42,48,52,67,75,78 and environmental factors (3.6%, n = 2 studies) 33,42 were the least studied.…”
Section: Resultsmentioning
confidence: 99%
“…The outcomes most commonly investigated were muscle function, 32,43,58,69,82 weight maintenance function (i.e. body weight), 34,55,58,74 intellectual function, 37,39,41,47,48,51,52 and mobility of joints and bone function 32,38,43,57,59,69,82,84 . The 38 studies retrieved on the activity component showed differences between levels of the GMFCS.…”
Section: Discussionmentioning
confidence: 99%
“…O GMFCS foi usado para classificar e estratificar os participantes em 51 (91,1%) dos 56 estudos; 16,17,31,33–49,51–70,72–75,77–81,83,84 14 estudos (25%) utilizaram o MACS, 32,39,41,42,50,53,61,68,71,75,79,80,82,84 e 3 estudos (5,4%) utilizaram o CFCS 36,53,68 . Nenhum dos estudos agrupou participantes usando o Sistema de Classificação das Habilidades de Comer e Beber (EDACS) ou o Sistema de Classificação da Função Visual (VFCS); apenas um estudo não utilizou nenhum sistema de classificação para agrupar crianças 76 .…”
Section: Resultsunclassified
“…16,48 These orthopaedic surgeons support that the best possible functional outcome is achieved before severe fixed muscle contractures and skeletal deformities are established, which are responsible for plateau or even falling of gross motor function level. 15,16,49 They also emphasise that the results of an orthopaedic surgery will be less effective, if this window of opportunity is lost and a complex decompensated joint-skeletal pathology has developed. 16 The delay in initiating orthopaedic surgery is usually mainly due to the reluctance of other paediatric specialists including physiotherapists and the family permitting earlier an orthopaedic surgery and solely exploring nonsurgical options.…”
Section: Selection Of An Appropriate Time For Orthopaedic Surgerymentioning
confidence: 99%